Method for preparing positive electrode active material and positive electrode active material

By controlling the distribution of zirconium and aluminum in the positive electrode active material of lithium-ion batteries, the problems of degradation of battery performance and uneven distribution of doped elements caused by the increase of nickel content are solved, and the initial resistance, life and thermal stability of the battery are improved.

CN119156722APending Publication Date: 2024-12-17LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040397.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-06-07
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The increase in the nickel content in the positive electrode active materials of existing lithium-ion batteries leads to changes in the oxidation state, resulting in a decline in battery performance, and the uneven distribution of doped elements leads to various problems of degradation in battery performance.

Method used

By adding a solution containing nickel, cobalt and manganese, a zirconium raw material and an ammonium cation complexing agent to the reactor for coprecipitation reaction, a composite transition metal hydroxide containing zirconium is prepared and mixed with lithium and aluminum raw materials are mixed with lithium and aluminum raw materials. Sintering controls the distribution of zirconium and aluminum to form lithium composite transition metal oxides to ensure that the internal aluminum and zirconium amount is higher than the surface amount.

Benefits of technology

Improves the initial resistance, life characteristics and thermal stability of the battery, reduces side reactions, and improves the cycle characteristics and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156722A_ABST
    Figure CN119156722A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a positive electrode active material and a positive electrode active material, and relates to a method for preparing a positive electrode active material and a positive electrode active material prepared by the preparation method, the method includes the steps of: (A) preparing a zirconium-containing composite transition metal hydroxide by adding a transition metal-containing solution containing at least one selected from nickel, cobalt and manganese, a zirconium-containing raw material, an ammonium cation complexing agent, and an alkaline solution to a reactor while performing a co-precipitation reaction; and (B) preparing a lithium composite transition metal oxide by mixing the zirconium-containing composite transition metal hydroxide with a lithium-containing raw material and an aluminum-containing raw material and sintering the mixture, wherein the lithium composite transition metal oxide contains zirconium, aluminum, and at least one selected from the group consisting of nickel, cobalt, and manganese.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0069033, filed on June 7, 2022, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The invention relates to a method for preparing a positive electrode active material and the positive electrode active material. Background Art

[0004] Recently, with the rapid market expansion of electric vehicles, the development of lithium-ion batteries has also been accelerated worldwide. Accordingly, electric vehicles are required to have high performance (such as mileage and output). Therefore, research is being conducted in the following direction: increasing the nickel content of NCM-type lithium composite transition metal oxides, which are the main materials of the positive electrode active material included in lithium-ion batteries. However, as the nickel content increases, the change from Ni to NCM according to the charging state occurs. 2+ To You 3+ or Ni 4+ oxidation, so rapid oxygen desorption occurs, and the desorbed oxygen and Ni 4+ This causes a side reaction with the electrolyte, thereby causing a problem of reducing battery performance such as life and resistance.

[0005] In order to solve this problem, there is a method of doping or coating by mixing a doping raw material or a coating raw material when mixing and sintering a positive electrode active material precursor and a lithium-containing raw material. However, since it is difficult to control the uniform distribution of the doping element and the coating element, and there is a problem of reducing various performances of the battery due to uneven reactions, improvement is needed. Summary of the invention

[0006] Technical issues

[0007] One aspect of the present invention provides a method for preparing a positive electrode active material, wherein, specifically, there is less zirconium present on the surface in an agglomerated state, and the amount of each of aluminum and zirconium present in the interior is higher than that on the surface.

[0008] Technical Solution

[0009] In order to solve the above problems, the present invention provides a method for preparing a positive electrode active material, a positive electrode active material, a positive electrode and a lithium secondary battery.

[0010] (1) The present invention provides a method for preparing a positive electrode active material, the method comprising the following steps:

[0011] (A) preparing a zirconium-containing composite transition metal hydroxide by adding a transition metal-containing solution containing at least one selected from nickel, cobalt and manganese, a zirconium-containing raw material, an ammonium cation complexing agent, and an alkaline solution into a reactor and performing a coprecipitation reaction; and

[0012] (B) preparing a lithium composite transition metal oxide by mixing a zirconium-containing composite transition metal hydroxide with a lithium-containing raw material and an aluminum-containing raw material and sintering the mixture,

[0013] The lithium composite transition metal oxide comprises zirconium, aluminum, and at least one selected from nickel, cobalt and manganese.

[0014] (2) The present invention provides the method for preparing a positive electrode active material according to (1) above, wherein the zirconium-containing raw material is at least one selected from zirconium hydroxide, zirconium sulfate, zirconium acetate, zirconium nitrate, zirconium halide, zirconium sulfide and zirconium oxyhydroxide.

[0015] (3) The present invention provides the method for preparing a positive electrode active material of (1) or (2) above, wherein the zirconium-containing raw material is added so that the amount of zirconium is 1,000 ppm to 9,000 ppm based on the total weight of the zirconium-containing composite transition metal hydroxide.

[0016] (4) The present invention provides a method for preparing a positive electrode active material according to any one of (1) to (3) above, wherein the aluminum-containing raw material is at least one selected from aluminum hydroxide, aluminum oxide, aluminum sulfate, aluminum acetate, aluminum nitrate, aluminum halide, aluminum sulfide and aluminum oxyhydroxide.

[0017] (5) The present invention provides the method for preparing a positive electrode active material according to any one of (1) to (4) above, wherein the aluminum-containing raw material is added so that the amount of aluminum is 1,000 ppm to 9,000 ppm based on the total weight of the lithium composite transition metal oxide.

[0018] (6) The present invention provides the method for preparing a positive electrode active material according to any one of (1) to (5) above, wherein the sintering in step (B) is performed at a temperature of 700°C to 800°C.

[0019] (7) The present invention provides a positive electrode active material, the positive electrode active material comprising a lithium composite transition metal oxide, the lithium composite transition metal oxide comprising zirconium, aluminum, and at least one selected from nickel, cobalt and manganese,

[0020] wherein the weight ratio of aluminum present in the interior to aluminum present on the surface is greater than 1.0, and

[0021] The weight ratio of zirconium present in the interior to zirconium present on the surface is greater than 1.0.

[0022] (8) The present invention provides the positive electrode active material of (7) above, wherein the zirconium content of the lithium composite transition metal oxide is 1,000 ppm to 9,000 ppm based on the total weight.

[0023] (9) The present invention provides the positive electrode active material of (7) or (8) above, wherein the aluminum content of the lithium composite transition metal oxide is 1,000 ppm to 9,000 ppm based on the total weight.

[0024] (10) The present invention provides the positive electrode active material according to any one of (7) to (9) above, wherein the average particle size (D 50 ) is 3 μm to 20 μm.

[0025] (11) The present invention provides a positive electrode comprising the positive electrode active material according to any one of (7) to (10) above.

[0026] (12) The present invention provides a lithium secondary battery, which includes the positive electrode of (11) above.

[0027] Beneficial Effects

[0028] According to the method for preparing a positive electrode active material of the present invention, a positive electrode active material can be provided in which there is less zirconium existing on the surface in an agglomerated state and the amounts of aluminum and zirconium each existing in the interior are higher than the amounts of aluminum and zirconium each existing on the surface.

[0029] Furthermore, the positive electrode active material according to the present invention can improve the performance of a battery when used in the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 (A) is the electron probe microanalysis (EPMA) data of the surface of the positive electrode active material of Example 1, Figure 1 (B) is the EPMA data of the interior of the positive electrode active material of Example 1.

[0031] Figure 2 (A) is the EPMA data of the surface of the positive electrode active material of Comparative Example 1, Figure 2 (B) is the EPMA data of the interior of the positive electrode active material of Comparative Example 1.

[0032] Figure 3 (A) is the EPMA data of the surface of the positive electrode active material of Comparative Example 4, Figure 3 (B) is the EPMA data of the interior of the positive electrode active material of Comparative Example 4. DETAILED DESCRIPTION

[0033] It should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries. In addition, it should be understood that based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the present invention, the words or terms should be interpreted as having meanings that are consistent with their meanings in the relevant technical background and the technical spirit of the present invention.

[0034] In addition, it should be understood that the terms "include", "comprises" or "has" in this specification specify the presence of the features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.

[0035] The term “on” in the present specification means not only a case where one member is directly formed on an upper surface of another member but also includes a case where an intermediate member may also exist.

[0036] In this specification, the expression "average particle size (D 50 )” represents the particle size at 50% of the volume cumulative distribution of the particle size. After dispersing the measurement target powder in a dispersion medium, the dispersion medium is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the difference in diffraction patterns due to the particle size when the particles pass through the laser beam, and the particle size distribution can be measured by calculating the particle size at 50% of the volume cumulative distribution of the particle size using the measuring instrument. 50 .

[0037] Hereinafter, the present invention will be described in more detail.

[0038] Method for preparing positive electrode active material

[0039] The present inventors have found that in the case where zirconium is first doped when preparing a composite transition metal hydroxide, since not only the distribution of zirconium in the finally prepared positive electrode active material can be controlled but also the distribution of aluminum added during sintering can be controlled, when the positive electrode active material is used in a battery, the performance of the battery is improved, thereby completing the present invention.

[0040] Generally, when it is desired to dope the positive electrode active material with a doping element, a method of mixing the doping element raw materials together and sintering them is used in the step of mixing and sintering the composite transition metal hydroxide precursor and the lithium-containing raw material, but the present invention is characterized in that by first doping the composite transition metal hydroxide precursor with zirconium, that is, by first doping zirconium during the preparation of the composite transition metal hydroxide, not only the distribution of zirconium can be controlled, but also the distribution of aluminum added in the step of mixing and sintering the precursor and the lithium-containing raw material can be controlled.

[0041] The present invention provides a method for preparing a positive electrode active material, the method comprising the following steps:

[0042] (A) preparing a zirconium-containing composite transition metal hydroxide by adding a transition metal-containing solution containing at least one selected from nickel, cobalt and manganese, a zirconium-containing raw material, an ammonium cation complexing agent, and an alkaline solution into a reactor and performing a coprecipitation reaction; and

[0043] (B) preparing a lithium composite transition metal oxide by mixing a zirconium-containing composite transition metal hydroxide with a lithium-containing raw material and an aluminum-containing raw material and sintering the mixture,

[0044] The lithium composite transition metal oxide comprises zirconium, aluminum, and at least one selected from nickel, cobalt and manganese.

[0045] The method for preparing a positive electrode active material according to the present invention may further include the following steps:

[0046] (C) The coating layer is formed by mixing a raw material containing a coating element with a lithium composite transition metal oxide and performing a heat treatment.

[0047] Each step of the method for preparing the positive electrode active material will be described in more detail below.

[0048] Step (A)

[0049] The method for preparing a positive electrode active material according to the present invention comprises the following steps:

[0050] (A) A zirconium-containing composite transition metal hydroxide is prepared by carrying out a coprecipitation reaction while adding a transition metal-containing solution containing at least one selected from nickel, cobalt and manganese, a zirconium-containing raw material, an ammonium cation complexing agent and an alkaline solution into a reactor.

[0051] Step A is a step of nucleating and growing composite transition metal hydroxide particles as a precursor of a positive electrode active material through a precipitation reaction while adding a transition metal-containing solution, a zirconium-containing raw material, an ammonium cation complexing agent and an alkaline solution into a reactor.

[0052] The solution containing transition metals may contain nickel (Ni) at 60 mol % or more of all metals. The solution containing transition metals may contain nickel (Ni) at 60 mol % or more, 70 mol % or more, 80 mol % or more, or 85 mol % or more of all metals to improve capacity.

[0053] The transition metal-containing solution may include at least one selected from a nickel raw material, a cobalt raw material, and a manganese raw material.

[0054] The nickel raw material can be nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxide, specifically Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, Ni(SO3)2 or a combination thereof, but the present invention is not limited thereto.

[0055] The cobalt raw material can be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxyl, specifically Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, Co(SO3)2 or a combination thereof, but the present invention is not limited thereto.

[0056] The manganese raw material can be a manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxide, specifically Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4, Mn(SO3)2, manganese acetate, manganese dicarboxylate, manganese citrate, fatty acid manganese salt, manganese oxyhydroxide, manganese chloride or a combination thereof, but the present invention is not limited thereto.

[0057] The transition metal-containing solution can be prepared by adding at least one selected from a nickel-containing raw material, a cobalt-containing raw material and a manganese-containing raw material to a solvent (specifically water or a mixed solvent of an organic solvent (such as alcohol, etc.) that can be uniformly mixed with water), but the present invention is not limited thereto.

[0058] According to the present invention, the zirconium-containing raw material may be at least one selected from zirconium hydroxide, zirconium sulfate, zirconium acetate, zirconium nitrate, zirconium halide, zirconium sulfide and zirconium oxyhydroxide. The zirconium-containing raw material may specifically be zirconium hydroxide, zirconium sulfate or a combination thereof, and more specifically may be zirconium sulfate. In this case, zirconium may be co-precipitated with the transition metal included in the transition metal-containing solution under the same conditions as the transition metal included in the transition metal-containing solution.

[0059] According to the present invention, the zirconium-containing raw material may be added so that the amount of zirconium is 1,000 ppm to 9,000 ppm, specifically 1,000 ppm, 1,500 ppm, 2,000 ppm or more, 7,000 ppm, 8,000 ppm or 9,000 ppm or less, based on the total weight of the zirconium-containing composite transition metal hydroxide. In this case, since the structural stability of the finally prepared positive electrode active material can be improved, the life characteristics can be further improved.

[0060] The zirconium-containing raw material may be added by being included in a transition metal-containing solution containing at least one selected from nickel, cobalt, and manganese. That is, the transition metal-containing solution may include zirconium and at least one selected from nickel, cobalt, and manganese.

[0061] The ammonium cation complexing agent may include, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3 or a combination thereof, but the present invention is not limited thereto. The ammonium cation complexing agent may also be used in the form of an aqueous solution, in which case a mixture of water or water and an organic solvent (e.g., alcohol) uniformly miscible with water may be used as a solvent.

[0062] The alkaline solution may include an alkali metal or alkaline earth metal hydroxide, such as NaOH, KOH or Ca(OH)2, a hydrate thereof or a combination thereof as a precipitant. The alkaline solution may also be used in the form of an aqueous solution, in which case water or a mixture of water and an organic solvent (e.g., alcohol) uniformly miscible with water may be used as a solvent.

[0063] The transition metal-containing solution, the zirconium-containing raw material, the ammonium cation complexing agent and the alkaline solution may be continuously added to the reactor.

[0064] The coprecipitation reaction may be carried out in an inert atmosphere. For example, the coprecipitation reaction may be carried out after nitrogen is blown into the reactor to remove dissolved oxygen.

[0065] The coprecipitation reaction may be performed at a pH of 12.0 to 13.0, specifically 12.0 to 12.5, and more specifically 12.0 to 12.2, in order to make the particle size of the composite transition metal hydroxide small and uniform.

[0066] The coprecipitation reaction may be performed at a temperature of 40° C. to 60° C., particularly 45° C. to 55° C., and more particularly 48° C. to 52° C. In the case where the coprecipitation reaction is performed at a temperature within the above range, since energy required for the coprecipitation reaction can be provided, the coprecipitation reaction can be smoothly performed.

[0067] The coprecipitation reaction may be carried out for 25 hours, 35 hours, 45 hours or more, and 60 hours, 70 hours or 80 hours or less. In this case, uniform particles can be formed.

[0068] As a result, the composition of the composite transition metal hydroxide prepared according to step (A) can be represented by Formula 1 below.

[0069] [Formula 1]

[0070] Ni a1 Co b1 Mn c1 Zrd1 M 1 e1 (OH)2

[0071] In Formula 1,

[0072] M 1 is at least one selected from boron (B), tungsten (W), magnesium (Mg), cerium (Ce), hafnium (Hf), tantalum (Ta), titanium (Ti), strontium (Sr), barium (Ba), cerium (Ce), hafnium (Hf), fluorine (F), phosphorus (P), sulfur (S), and lanthanum (La), and

[0073] 0.60 ≤ a1 < 1.0, 0 < b1 ≤ 0.40, 0 < c1 ≤ 0.40, 0 < d1 ≤ 0.10, 0 ≤ e1 ≤ 0.10 and a1 + b1 + c1 + d1 + e1 = 1.

[0074] a1 represents the atomic fraction of nickel in the metal elements of the composite transition metal hydroxide, where a1 can be 0.60, 0.70, 0.80, above 0.85, below 0.95 or 0.98.

[0075] b1 represents the atomic fraction of cobalt in the metal elements of the composite transition metal hydroxide, where b1 can be 0.01, 0.02, 0.03 or above, 0.10, 0.30 or 0.40 or below.

[0076] c1 represents the atomic fraction of manganese in the metal elements of the composite transition metal hydroxide, where c1 can be 0.01, 0.02, 0.03 or above, 0.10, 0.30 or 0.40 or below.

[0077] d1 represents the atomic fraction of zirconium in the metal elements of the composite transition metal hydroxide, where d1 can be greater than 0, 0.01 or above, 0.02, 0.05 or 0.10 or below.

[0078] e1 represents the atomic fraction of element M 1 in the metal elements of the composite transition metal hydroxide, where e1 can be 0, 0.01 or above, 0.02, 0.05 or 0.10 or below.

[0079] In the case where the transition metal-containing solution further includes ions of element M 1 , the transition metal-containing solution can be prepared by adding raw materials containing element M 1 together to a solvent.

[0080] Step (B)

[0081] The method for preparing a positive electrode active material according to the present invention comprises the following steps: (B) preparing a lithium composite transition metal oxide by mixing a zirconium-containing composite transition metal hydroxide with a lithium-containing raw material and an aluminum-containing raw material and sintering the mixture. In this case, the lithium composite transition metal oxide comprises zirconium, aluminum, and at least one selected from nickel, cobalt, and manganese.

[0082] According to the present invention, since the composite transition metal hydroxide contains zirconium, the distribution of aluminum in the lithium composite transition metal oxide prepared by sintering of step (B) can be controlled, and the weight ratio of aluminum present in the interior to aluminum present on the surface of the prepared lithium composite transition metal oxide can be greater than 1.0, and the weight ratio of zirconium present in the interior to zirconium present on the surface can be greater than 1.0. Therefore, the initial resistance (initial direct current internal resistance (DCIR)) characteristics, life characteristics and thermal stability of the battery including the positive electrode active material prepared according to the present invention can all be improved. The surface can be a region within 1 μm from the outermost portion of the lithium composite transition metal oxide.

[0083] The lithium-containing raw material can be a lithium-containing carbonate (such as lithium carbonate, etc.), hydrate (such as lithium hydroxide hydrate (LiOH·H2O), etc.), hydroxide (such as lithium hydroxide, etc.), nitrate (such as lithium nitrate (LiNO3)), etc.) or chloride (such as lithium chloride (LiCl)).

[0084] The aluminum-containing raw material is added to improve the initial resistance characteristics, life characteristics and thermal stability of the battery. The aluminum-containing raw material can be an aluminum-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxide.

[0085] According to the present invention, the aluminum-containing raw material can be at least one selected from aluminum hydroxide, aluminum oxide, aluminum sulfate, aluminum acetate, aluminum nitrate, aluminum halide, aluminum sulfide and aluminum oxyhydroxide. The aluminum-containing raw material can specifically be aluminum hydroxide, aluminum oxide or a combination thereof, more specifically aluminum hydroxide.

[0086] According to the present invention, the aluminum-containing raw material may be added so that the amount of aluminum is 1,000 ppm to 9,000 ppm, specifically 1,000 ppm, 1,500 ppm, 2,000 ppm or more, 7,000 ppm, 8,000 ppm or 9,000 ppm or less, based on the total weight of the lithium composite transition metal oxide. In this case, since the side reaction between the obtained positive electrode active material and the electrolyte can be reduced, the degradation of the positive electrode active material can be suppressed.

[0087] The mixing of the zirconium-containing composite transition metal hydroxide, the lithium-containing raw material, and the aluminum-containing raw material can be carried out by solid-phase mixing. In addition, the mixing ratio of the composite transition metal hydroxide and the lithium-containing raw material can be determined within the range that satisfies the atomic fractions of the respective components in the finally prepared positive electrode active material. For example, the mixing amounts of the composite transition metal hydroxide and the lithium-containing raw material can make the molar ratio of transition metal:Li within the range of 1:0.9 to 1:1.2, specifically within the range of 1:0.95 to 1:1.1. When the composite transition metal hydroxide and the lithium-containing raw material are mixed within the above range, a positive electrode active material exhibiting excellent capacity characteristics can be prepared.

[0088] According to the present invention, the sintering in step (B) can be carried out at a temperature of 680 °C to 900 °C, specifically 680 °C, 690 °C, 700 °C or higher, and 870 °C, 880 °C, 890 °C, 900 °C or lower. In this case, a positive electrode active material exhibiting excellent capacity characteristics can be prepared.

[0089] The sintering can be carried out in an oxygen atmosphere to enable a stable reaction between lithium and the transition metal (especially nickel) and form a stable structure.

[0090] The sintering can be carried out for 15 hours, 17 hours, 20 hours or more, and 30 hours, 33 hours or 35 hours or less. In this case, since a layered structure can be stably formed, a positive electrode active material exhibiting excellent capacity characteristics can be prepared.

[0091] As a result, the composition of the lithium composite transition metal oxide prepared according to step (B) can be represented by the following formula 2.

[0092] [Formula 2]

[0093] Li 1+x Ni a2 Co b2 Mn c2 Zr d2 Al e2 M 2 f2 O2

[0094] In formula 2,

[0095] M 2 is at least one selected from B, W, Mg, Ce, Hf, Ta, Ti, Sr, Ba, Ce, Hf, F, P, S, and La, and

[0096] 0.60 ≤ a2 < 1.0, 0 < b2 ≤ 0.40, 0 < c2 ≤ 0.40, 0 < d2 ≤ 0.10, 0 < e2 ≤ 0.10, 0 ≤ f2 ≤ 0.10 and a2 + b2 + c2 + d2 + e2 + f2 = 1.

[0097] a2 represents the atomic fraction of nickel in the metal elements in the lithium composite transition metal oxide, wherein a2 may be 0.60, 0.70, 0.80, 0.85 or more and 0.95 or 0.98 or less.

[0098] b2 represents the atomic fraction of cobalt in the metal elements in the lithium composite transition metal oxide, wherein b2 may be 0.01, 0.02, 0.03 or more and 0.10, 0.30 or 0.40 or less.

[0099] c2 represents the atomic fraction of manganese in the metal elements in the lithium composite transition metal oxide, wherein c2 may be 0.01, 0.02, 0.03 or more and 0.10, 0.30 or 0.40 or less.

[0100] d2 represents the atomic fraction of zirconium in the metal elements in the lithium composite transition metal oxide, wherein d2 may be greater than 0, greater than 0.01, 0.02, 0.05 or less than 0.10.

[0101] e2 represents the atomic fraction of aluminum in the metal elements in the lithium composite transition metal oxide, wherein e2 may be greater than 0, greater than 0.01, 0.02, 0.05 or less than 0.10.

[0102] f2 represents the element M in the metal element in the lithium composite transition metal oxide 2 Atomic fraction, where f2 can be 0, greater than 0.01, 0.02, 0.05 or less than 0.10.

[0103] Step (C)

[0104] The method for preparing a positive electrode active material according to the present invention may further include the following steps: (C) forming a coating layer by mixing a raw material containing a coating element with a lithium composite transition metal oxide and performing a heat treatment.

[0105] The metal element included in the raw material containing the coating element may be B, W, molybdenum (Mo), chromium (Cr), niobium (Nb), Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, F, P, S and yttrium (Y). The raw material containing the coating element may be an acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxide containing the metal element. For example, in the case where the metal element is B, boric acid (H3BO3) or the like may be used.

[0106] The raw material containing the coating element may be included in an amount of 200 ppm to 2,000 ppm by weight based on the lithium transition metal oxide. In the case where the amount of the raw material containing the coating element is within the above range, the capacity of the battery may be improved, and the direct reaction between the electrolyte and the lithium transition metal oxide may be suppressed by the formed coating, and the long-term performance characteristics of the battery may be improved.

[0107] The heat treatment of step (C) may be performed at a temperature of 200° C. to 400° C. In the case where the heat treatment temperature is within the above range, a coating layer may be formed while maintaining the structural stability of the transition metal oxide. The heat treatment of step (C) may be performed for 1 to 10 hours. In the case where the heat treatment time is within the above range, an appropriate coating layer may be formed and production efficiency may be improved.

[0108] Positive electrode active material

[0109] The present invention provides a positive electrode active material, the positive electrode active material comprises a lithium composite transition metal oxide, the lithium composite transition metal oxide comprises zirconium, aluminum, and at least one selected from nickel, cobalt and manganese,

[0110] wherein the weight ratio of aluminum present in the interior to aluminum present on the surface is greater than 1.0, and

[0111] The weight ratio of zirconium present in the interior to zirconium present on the surface is greater than 1.0.

[0112] The positive electrode active material according to the present invention can be prepared by the method for preparing a positive electrode active material as described above. In addition, the composition of the lithium composite transition metal oxide can be represented by Formula 2. The surface can be a region within 1 μm from the outermost portion of the lithium composite transition metal oxide.

[0113] Since the lithium composite transition metal oxide includes both zirconium and aluminum, it not only improves the structural stability, but also can be used as an HF scavenger, and the life characteristics, resistance characteristics and thermal stability of the battery can all be improved. In the case where the lithium composite transition metal oxide does not include zirconium, there is a problem of degradation of the life and storage characteristics due to decreased structural stability, and in the case where the lithium composite transition metal oxide does not include aluminum, there is a problem of decreased thermal stability of the battery, decreased life characteristics and increased resistance due to degradation such as increased side reactions.

[0114] If the weight ratio of aluminum present in the interior to aluminum present on the surface is greater than 1.0, the side reaction with the electrolyte is reduced, thereby improving the cycle characteristics, but if the weight ratio is below 1.0, the degradation of the positive electrode active material is accelerated by the side reaction with the electrolyte, resulting in a problem of reduced cycle characteristics.

[0115] If the weight ratio of zirconium present inside to zirconium present on the surface is greater than 1.0, it contributes to lattice stabilization, thereby improving the cycle characteristics. However, if the weight ratio is 1.0 or less, there is a problem that the zirconia present on the surface increases, thereby increasing the resistance.

[0116] According to the present invention, the zirconium content of the lithium composite transition metal oxide can be 1,000 ppm to 9,000 ppm, specifically 1,000 ppm, 1,500 ppm, 2,000 ppm or more, 7,000 ppm, 8,000 ppm or 9,000 ppm or less. In this case, since the structural stability increases, the life characteristics can be improved.

[0117] According to the present invention, the aluminum content of the lithium composite transition metal oxide can be 1,000 ppm to 9,000 ppm, specifically 1,000 ppm, 1,500 ppm, 2,000 ppm or more, 7,000 ppm, 8,000 ppm or 9,000 ppm or less. In this case, since the side reaction with the electrolyte is reduced, the deterioration of the positive electrode active material can be suppressed.

[0118] According to the present invention, the composition of the lithium composite transition metal oxide can be represented by the following formula 2.

[0119] [Formula 2]

[0120] Li 1+x Ni a2 Co b2 Mn c2 Zr d2 Al e2 M 2 f2 O2

[0121] In Formula 2,

[0122] M 2 is at least one selected from B, W, Mg, Ce, Hf, Ta, Ti, Sr, Ba, Ce, Hf, F, P, S and La, and

[0123] 0.60 ≤ a2 < 1.0, 0 < b2 ≤ 0.40, 0 < c2 ≤ 0.40, 0 < d2 ≤ 0.10, 0 < e2 ≤ 0.10, 0 ≤ f2 ≤ 0.10 and a2 + b2 + c2 + d2 + e2 + f2 = 1.

[0124] a2 represents the atomic fraction of nickel among the metal elements in the lithium composite transition metal oxide, where a2 can be 0.60, 0.70, 0.80, 0.85 or more, 0.95 or 0.98 or less.

[0125] b2 represents the atomic fraction of cobalt in the metal elements in the lithium composite transition metal oxide, wherein b2 may be 0.01, 0.02, 0.03 or more and 0.10, 0.30 or 0.40 or less.

[0126] c2 represents the atomic fraction of manganese in the metal elements in the lithium composite transition metal oxide, wherein c2 may be 0.01, 0.02, 0.03 or more and 0.10, 0.30 or 0.40 or less.

[0127] d2 represents the atomic fraction of zirconium in the metal elements in the lithium composite transition metal oxide, wherein d2 may be greater than 0, greater than 0.01, 0.02, 0.05 or less than 0.10.

[0128] e2 represents the atomic fraction of aluminum in the metal elements in the lithium composite transition metal oxide, wherein e2 may be greater than 0, greater than 0.01, 0.02, 0.05 or less than 0.10.

[0129] f2 represents the element M in the metal element in the lithium composite transition metal oxide 2 Atomic fraction, where f2 can be 0, greater than 0.01, 0.02, 0.05 or less than 0.10.

[0130] According to the present invention, the average particle size (D 50 ) may be 3 μm to 20 μm, specifically 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or more, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm or less. In this case, the performance of the battery can be further improved.

[0131] positive electrode

[0132] Furthermore, the present invention may provide a positive electrode for a lithium secondary battery, the positive electrode for a lithium secondary battery comprising the positive electrode active material described above.

[0133] Specifically, the positive electrode includes a positive electrode collector and a positive electrode active material layer provided on at least one surface of the positive electrode collector and including the positive electrode active material.

[0134] There is no particular limitation on the positive electrode current collector, as long as it has conductivity and does not cause adverse chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0135] The positive electrode active material layer may include a conductive material and a binder as well as a positive electrode active material.

[0136] In this case, the content of the positive electrode active material may be 80 wt % to 99 wt %, more specifically 85 wt % to 98 wt % based on the total weight of the positive electrode active material layer. When the content of the positive electrode active material is within the above range, excellent capacity characteristics may be obtained.

[0137] In this case, the conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of conductive materials can be graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; metals such as copper, nickel, aluminum and silver powder or fiber; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof can be used. Based on the total weight of the positive electrode active material layer, the content of the conductive material can be 1 wt % to 30 wt %.

[0138] The binder improves the adhesion between the positive active material particles and the adhesion between the positive active material and the collector. The specific example of the binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used. Based on the gross weight of the positive active material layer, the content of the binder can be 1 wt % to 30 wt %.

[0139] The positive electrode can be prepared according to a typical method for preparing a positive electrode, except that the above-mentioned positive electrode active material is used. Specifically, the positive electrode material mixture is coated on the positive electrode current collector, and then the positive electrode can be prepared by drying and rolling the coated positive electrode current collector, and the positive electrode material mixture is prepared by dissolving or dispersing the positive electrode active material and the optional binder and conductive material in a solvent. In this case, the type and amount of the positive electrode active material, binder and conductive material are the same as those described above. In addition, as another method, the positive electrode can be prepared by casting the positive electrode material mixture on a separate carrier, and then stacking the film separated from the carrier on the positive electrode collector.

[0140] The solvent may be a commonly used solvent in the art, and may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, any one of which or a mixture of two or more thereof may be used. Considering the coating thickness and manufacturing yield of the slurry, if the solvent can dissolve or disperse the positive electrode active material, the conductive material and the binder, and can be made to have a viscosity that can provide excellent thickness uniformity during subsequent coating for preparing the positive electrode, the amount of the solvent may be sufficient.

[0141] Lithium secondary battery

[0142] In addition, an electrochemical device including a positive electrode can be prepared in the present invention. The electrochemical device can be specifically a battery or a capacitor, and more specifically a lithium secondary battery.

[0143] The lithium secondary battery specifically includes a positive electrode, a negative electrode disposed to face the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is the same as above, its detailed description will be omitted, and only the remaining configuration will be described in detail below.

[0144] In addition, the lithium secondary battery may further optionally include a battery container accommodating an electrode assembly of a positive electrode, a negative electrode, and a separator, and a sealing member sealing the battery container.

[0145] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0146] There is no particular limitation on the negative electrode current collector, as long as it has high conductivity and does not cause adverse chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy can be used. In addition, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and similar to the positive electrode current collector, fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0147] The negative electrode active material layer optionally includes a binder and a conductive material in addition to the negative electrode active material.

[0148] Compounds capable of reversibly intercalating and deintercalating lithium can be used as negative electrode active materials. Specific examples of negative electrode active materials may be carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; (semi)metallic materials that can be alloyed with lithium, such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys; (semi)metallic oxides that can be doped and dedoped with lithium, such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite material including a (semi)metal material and a carbonaceous material, such as a Si-C composite material or a Sn-C composite material, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon can be soft carbon and hard carbon, and typical examples of high-crystalline carbon can be irregular, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-type carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch.

[0149] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0150] The binder is a component that helps to bind the conductive material, the active material and the current collector, wherein the binder is generally added in an amount of 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of the binder may be polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber and various copolymers thereof.

[0151] The conductive material is a component for further improving the conductivity of the negative electrode active material, wherein the amount of the conductive material added may be 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. There is no particular limitation on the conductive material, as long as it has conductivity and does not cause adverse chemical changes in the battery, for example, conductive materials such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0152] The negative electrode active material layer can be prepared by coating a negative electrode material mixture on a negative electrode collector and drying the coated negative electrode collector, or by casting the negative electrode material mixture on a separate carrier and then stacking the film separated from the carrier on the negative electrode collector, wherein the negative electrode material mixture is prepared by dissolving or dispersing an optional binder and a conductive material and the negative electrode active material in a solvent.

[0153] In a lithium secondary battery, a separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used in lithium secondary batteries, in particular, a separator having high moisture retention capacity for electrolytes and low resistance to electrolyte ion transfer is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure having two or more layers thereof. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be optionally used.

[0154] In addition, the electrolyte used in the present invention may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery, but the present invention is not limited thereto.

[0155] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0156] Any organic solvent can be used as the organic solvent without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group and may include a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents are preferred, and a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ion conductivity and high dielectric constant that can improve the charge / discharge performance of the battery and low viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) is more preferred. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.

[0157] Lithium salts can be used without particular limitation, as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2 can be used as lithium salts. Lithium salts can be used in a concentration range of 0.1 M to 2.0 M. Since the electrolyte can have appropriate conductivity and viscosity when the lithium salt concentration is included in the above range, excellent electrolyte performance can be obtained, and lithium ions can be effectively moved.

[0158] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, in addition to the electrolyte components, the electrolyte may also include at least one additive, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, the content of the additive may be 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0159] As described above, since the lithium secondary battery including the positive electrode active material according to the present invention exhibits high initial efficiency, low initial resistance, excellent cycle characteristics and thermal stability, the lithium secondary battery is suitable for portable devices such as mobile phones, notebook computers and digital cameras; and electric vehicles such as hybrid electric vehicles (HEV).

[0160] Therefore, according to another embodiment of the present invention, there are provided a battery module including a lithium secondary battery as a unit cell and a battery pack including the battery module.

[0161] The battery module or battery pack may be used as a power source for at least one of the following medium to large devices: a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0162] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical type using a can, a prismatic type, a pouch type, or a coin type may be used.

[0163] The lithium secondary battery according to the present invention can be used not only in a battery cell used as a power source for small devices but also as a unit battery in a medium or large battery module including a plurality of battery cells.

[0164] Preferred Embodiments

[0165] The following will describe in detail embodiments of the present invention in a manner that a person skilled in the art can easily carry out the present invention. However, the present invention can be implemented in many different forms and should not be construed as being limited to the embodiments described herein.

[0166] Examples and Comparative Examples

[0167] Example 1

[0168] NiSO4, CoSO4, MnSO4 and Zr(SO4)2 were mixed in deionized water in an amount such that the molar ratio of nickel:cobalt:manganese:zirconium was 93.6:2:4:0.4 to prepare a transition metal aqueous solution with a concentration of 2.4 M. In addition, a NaOH aqueous solution with a concentration of 25 wt% and an NH4OH aqueous solution with a concentration of 9 wt% were prepared. For reference, Zr(SO4)2 was added so that the amount of zirconium was 4,500 ppm based on the total weight of the prepared positive electrode active material precursor.

[0169] After 82.8 L of deionized water was placed in the reactor, the dissolved oxygen in the water was removed by purging the reactor with nitrogen at a rate of 20 L / min, thereby establishing a non-oxidizing atmosphere in the reactor. Thereafter, after adding 158 mL of an aqueous NaOH solution and 6,812 mL of an aqueous NH4OH solution, the mixture was stirred at 50°C at a stirring speed of 250 rpm to adjust the pH in the reactor to a range of 12.0 to 12.2.

[0170] Thereafter, while stirring at a stirring speed of 650 rpm, a coprecipitation reaction was carried out at 50° C. and a pH of 11.6 while continuously adding a transition metal aqueous solution, a NaOH aqueous solution, and an NH 4 OH aqueous solution at rates of 23.9 L / hour, 14.4 L / hour, and 3.38 L / hour, respectively, to prepare a Ni 0.936 Co 0.02 Mn 0.04 Zr 0.004 (OH)2 positive electrode active material precursor.

[0171] The positive electrode active material precursor, LiOH and Al(OH)3 were mixed in a molar ratio of 1:1.05:0.015 and sintered at 755°C for 27 hours in an oxygen atmosphere to prepare a positive electrode active material (average particle size (D 50 ): 13 μm). In this case, the positive electrode active material includes 4,000 ppm of zirconium and 4,000 ppm of aluminum based on the total weight.

[0172] Example 2

[0173] NiSO4, CoSO4, MnSO4 and Zr(SO4)2 were mixed in deionized water in an amount such that the molar ratio of nickel:cobalt:manganese:zirconium was 94.6:2:3:0.4 to prepare a transition metal aqueous solution with a concentration of 2.4 M. In addition, a NaOH aqueous solution with a concentration of 25 wt% and an NH4OH aqueous solution with a concentration of 9 wt% were prepared. For reference, Zr(SO4)2 was added so that the amount of zirconium was 4,500 ppm based on the total weight of the prepared positive electrode active material precursor.

[0174] After 82.8 L of deionized water was placed in the reactor, the dissolved oxygen in the water was removed by purging the reactor with nitrogen at a rate of 20 L / min, thereby establishing a non-oxidizing atmosphere in the reactor. Thereafter, after adding 158 mL of an aqueous NaOH solution and 6,812 mL of an aqueous NH4OH solution, the mixture was stirred at 50°C at a stirring speed of 250 rpm to adjust the pH in the reactor to a range of 12.0 to 12.2.

[0175] Thereafter, while stirring at a stirring speed of 650 rpm, a coprecipitation reaction was carried out at 50° C. and a pH of 11.6 while continuously adding a transition metal aqueous solution, a NaOH aqueous solution, and an NH 4 OH aqueous solution at rates of 23.9 L / hour, 14.4 L / hour, and 3.38 L / hour, respectively, to prepare a Ni 0.946 Co 0.02 Mn 0.03 Zr 0.004 (OH)2 positive electrode active material precursor.

[0176] The positive electrode active material precursor, LiOH and Al(OH)3 were mixed in a molar ratio of 1:1.05:0.015 and sintered at 735 °C for 27 hours in an oxygen atmosphere to prepare a positive electrode active material (average particle size (D 50 ): 15 μm). In this case, the positive electrode active material includes 4,000 ppm of zirconium and 4,000 ppm of aluminum based on the total weight.

[0177] Example 3

[0178] In the same manner as in Example 1, a 0.936 Co 0.02 Mn 0.04 Zr 0.004 (OH)2 positive electrode active material precursor.

[0179] The positive electrode active material precursor, LiOH and Al(OH)3 were mixed in a molar ratio of 1:1.05:0.010 and sintered at 755°C for 27 hours in an oxygen atmosphere to prepare a positive electrode active material (average particle size (D 50 ): 13 μm). In this case, the positive electrode active material includes 4,000 ppm of zirconium and 2,500 ppm of aluminum based on the total weight.

[0180] Comparative Example 1

[0181] NiSO4, CoSO4 and MnSO4 were mixed in deionized water in an amount such that the molar ratio of nickel:cobalt:manganese was 94:2:4 to prepare a transition metal aqueous solution with a concentration of 2.4 M. In addition, a NaOH aqueous solution with a concentration of 25 wt% and an NH4OH aqueous solution with a concentration of 9 wt% were prepared.

[0182] After 82.8 L of deionized water was placed in the reactor, the dissolved oxygen in the water was removed by purging the reactor with nitrogen at a rate of 20 L / min, thereby establishing a non-oxidizing atmosphere in the reactor. Thereafter, after adding 158 mL of an aqueous NaOH solution and 6,812 mL of an aqueous NH4OH solution, the mixture was stirred at 50°C at a stirring speed of 250 rpm to adjust the pH in the reactor to a range of 12.0 to 12.2.

[0183] Thereafter, while stirring at a stirring speed of 650 rpm, a coprecipitation reaction was carried out at 50° C. and a pH of 11.6 while continuously adding a transition metal aqueous solution, a NaOH aqueous solution, and an NH 4 OH aqueous solution at rates of 23.9 L / hour, 14.4 L / hour, and 3.38 L / hour, respectively, to prepare a Ni 0.94 Co 0.02 Mn 0.04 (OH)2 positive electrode active material precursor.

[0184] The positive electrode active material precursor, LiOH, Al(OH)3 and ZrO2 were mixed in a molar ratio of 1:1.05:0.015:0.004 and sintered at 755°C for 27 hours in an oxygen atmosphere to prepare a positive electrode active material (average particle size (D 50 ): 13 μm). In this case, the positive electrode active material includes 4,000 ppm of zirconium and 4,000 ppm of aluminum based on the total weight.

[0185] Comparative Example 2

[0186] NiSO4, CoSO4 and MnSO4 were mixed in deionized water in an amount such that the molar ratio of nickel:cobalt:manganese was 95:2:3 to prepare a transition metal aqueous solution with a concentration of 2.4 M. In addition, a NaOH aqueous solution with a concentration of 25 wt% and an NH4OH aqueous solution with a concentration of 9 wt% were prepared.

[0187] After 82.8 L of deionized water was placed in the reactor, the dissolved oxygen in the water was removed by purging the reactor with nitrogen at a rate of 20 L / min, thereby establishing a non-oxidizing atmosphere in the reactor. Thereafter, after adding 158 mL of an aqueous NaOH solution and 6,812 mL of an aqueous NH4OH solution, the mixture was stirred at 50°C at a stirring speed of 250 rpm to adjust the pH in the reactor to a range of 12.0 to 12.2.

[0188] Thereafter, while stirring at a stirring speed of 650 rpm, a coprecipitation reaction was carried out at 50° C. and a pH of 11.6 while continuously adding a transition metal aqueous solution, a NaOH aqueous solution, and an NH 4 OH aqueous solution at rates of 23.9 L / hour, 14.4 L / hour, and 3.38 L / hour, respectively, to prepare a Ni 0.95 Co 0.02 Mn 0.03 (OH)2 positive electrode active material precursor.

[0189] The positive electrode active material precursor, LiOH, Al(OH)3 and ZrO2 were mixed in a molar ratio of 1:1.05:0.015:0.004 and sintered at 735°C for 27 hours in an oxygen atmosphere to prepare a positive electrode active material (average particle size (D 50 ): 15 μm). In this case, the positive electrode active material includes 4,000 ppm of zirconium and 4,000 ppm of aluminum based on the total weight.

[0190] Comparative Example 3

[0191] In the same manner as in Example 1, a 0.936 Co 0.02 Mn 0.04 Zr 0.004 (OH)2 positive electrode active material precursor.

[0192] The cathode active material precursor and LiOH were mixed at a molar ratio of 1:1.05 and sintered at 755 °C for 27 h in an oxygen atmosphere to prepare a cathode active material (average particle size (D 50 ): 13 μm). In this case, the positive electrode active material includes 4,000 ppm of zirconium based on the total weight.

[0193] Comparative Example 4

[0194] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in deionized water in an amount such that the molar ratio of nickel:cobalt:manganese:aluminum was 92.5:2:6:1.5 to prepare a transition metal aqueous solution with a concentration of 2.4 M. In addition, a NaOH aqueous solution with a concentration of 25 wt% and an NH4OH aqueous solution with a concentration of 9 wt% were prepared. For reference, Al2(SO4)3 was added so that the amount of aluminum was 4,000 ppm based on the total weight of the prepared positive electrode active material precursor.

[0195] After 82.8 L of deionized water was placed in the reactor, the dissolved oxygen in the water was removed by purging the reactor with nitrogen at a rate of 20 L / min, thereby establishing a non-oxidizing atmosphere in the reactor. Thereafter, after adding 158 mL of an aqueous NaOH solution and 6,812 mL of an aqueous NH4OH solution, the mixture was stirred at 50°C at a stirring speed of 250 rpm to adjust the pH in the reactor to a range of 12.0 to 12.2.

[0196] Thereafter, while stirring at a stirring speed of 650 rpm, a coprecipitation reaction was carried out at 50° C. and a pH of 11.6 while continuously adding a transition metal aqueous solution, a NaOH aqueous solution, and an NH 4 OH aqueous solution at rates of 23.9 L / hour, 14.4 L / hour, and 3.38 L / hour, respectively, to prepare a Ni 0.925 Co 0.02 Mn 0.04 Al 0.015 (OH)2 positive electrode active material precursor.

[0197] The positive electrode active material precursor, LiOH and ZrO2 were mixed in a molar ratio of 1:1.05:0.004 and sintered at 755 °C for 27 hours in an oxygen atmosphere to prepare a positive electrode active material (average particle size (D 50 ): 13 μm). In this case, the positive electrode active material includes 4,000 ppm of zirconium and 4,000 ppm of aluminum based on the total weight.

[0198] Experimental example

[0199] Experimental Example 1: Surface and Internal Composition Analysis of Positive Electrode Active Materials

[0200] The amount (wt %) of Al and Zr elements present in the interior and on the surface of each positive electrode active material of Example 1, Comparative Example 1 and Comparative Example 4 was confirmed by using EPMA (Electron Probe Micro Analyzer) (JXA-8350F, JEOL Co., Ltd.) (accelerating voltage: 15 kV, probe current: 100 nA), and the results are shown in Table 1. When confirming the amount of Al and Zr elements present in the interior of the positive electrode active material, the positive electrode active material was cut by ion milling (IM4000, HITACHI), and then the cross section was analyzed.

[0201] Specifically, the amount of elements present on the surface of each positive electrode active material of Example 1, Comparative Example 1 and Comparative Example 4 was determined by Figure 1 The value obtained by EPMA mapping of the entire surface image of the positive electrode active material of Example 1 in (A) is obtained by Figure 2 The values ​​obtained by EPMA mapping of the entire surface image of the positive electrode active material of Comparative Example 1 in (A) and Figure 3 The value obtained by performing EPMA mapping on the entire surface image of the positive electrode active material of Comparative Example 4 in (A). In addition, the amount of elements present in the interior of each positive electrode active material of Example 1, Comparative Example 1 and Comparative Example 4 was calculated by Figure 1 The average value of the values ​​obtained by EPMA mapping the interior of each red square in the cross-sectional image of the positive electrode active material of Example 1 in (B) is obtained by Figure 2 The average of the values ​​obtained by EPMA mapping the interior of each square 1 to 6 in the cross-sectional image of the positive electrode active material of Comparative Example 1 in (B), and the average of the values ​​obtained by Figure 3 The average value of the values ​​obtained by performing EPMA mapping on the interior of each square 1 to 8 in the cross-sectional image of each positive electrode active material of Comparative Example 4 in (B) .

[0202] Figure 1 (A) is an EPMA mapping image of the surface of the positive electrode active material of Example 1, Figure 1 (B) is an EPMA mapping image of a cross section of the positive electrode active material of Example 1. Figure 2 (A) is an EPMA mapping image of the surface of the positive electrode active material of Comparative Example 1, Figure 2 (B) is an EPMA mapping image of a cross section of the positive electrode active material of Comparative Example 1. Figure 3 (A) is an EPMA mapping image of the surface of the positive electrode active material of Comparative Example 4, Figure 3 (B) is an EPMA mapping image of a cross section of the positive electrode active material of Comparative Example 4.

[0203]

[0204] refer to Figures 1 to 3 From Table 1, it can be confirmed that the positive electrode active material of Example 1 has less zirconium present on the surface in an agglomerated state, and the amount of each of aluminum and zirconium present in the interior is higher than the amount of each of aluminum and zirconium present on the surface. On the contrary, it can be confirmed that the positive electrode active materials of Comparative Examples 1 and 4 have a large amount of zirconium present on the surface in an agglomerated state, and a larger amount of aluminum and zirconium elements exist on the surface of the positive electrode active materials than in the examples.

[0205] Experimental Example 2: Battery Performance Evaluation

[0206] Lithium secondary batteries were prepared using the cathode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4, and initial efficiency, initial resistance (DCIR), capacity retention rate, resistance increase rate, and DSC onset temperature were evaluated for each lithium secondary battery.

[0207] Specifically, the positive electrode slurry was prepared by mixing each positive electrode active material prepared in Examples 1 to 3 and Comparative Examples 1 to 4, SuperC 65 conductive material, and KF1120 binder in an N-methylpyrrolidone (NMP) solvent in a weight ratio of 96.5: 1.5: 2.0. One surface of the aluminum current collector was coated with the positive electrode slurry, dried at 130 ° C, and then rolled to prepare the positive electrode. A lithium (Li) metal disk was used as the negative electrode active material. After preparing the electrode assembly by arranging a separator between the positive and negative electrodes prepared above, each lithium secondary battery was prepared by arranging the electrode assembly in a battery case and then injecting an electrolyte into the battery case. In this case, an electrolyte of 1 M LiPF6 dissolved in an organic solvent of EC / EMC / DMC (3 / 3 / 4, volume %) was injected as an electrolyte to prepare a lithium secondary battery.

[0208] Each lithium secondary battery prepared as described above was charged to 4.25 V at a constant current of 0.2 C and discharged to 2.5 V at a constant current of 0.2 C at 25° C., and the initial charge capacity and the initial discharge capacity were obtained, and the percentage of the initial discharge capacity relative to the initial charge capacity was set as the initial efficiency (%), and the initial efficiency was shown in the following Table 2. In this case, the current and voltage at 60 seconds after the start of discharge were measured, and the initial resistance value was calculated by the formula R=I / V and is shown in the following Table 2.

[0209] In addition, each lithium secondary battery prepared as described above was charged to 4.25 V at a constant current of 0.33 C at 45° C. and each lithium secondary battery was discharged to 2.5 V at a constant current of 0.33 C, which was set as one cycle, and the cycle was repeated 30 times, and the percentage of the discharge capacity in the 30th cycle relative to the discharge capacity in the first cycle was set as the capacity retention rate (%) and shown in the following Table 2, and the resistance in the 30th cycle relative to the resistance in the first cycle was set as the resistance increase rate (%) and shown in the following Table 2. For reference, the current and voltage at 60 seconds after the start of discharge in each cycle were measured, and the resistance value was calculated by the formula R=I / V.

[0210] In addition, thermal stability was evaluated as follows. Specifically, each lithium secondary battery prepared as described above was charged to 4.25 V at a constant current of 0.2 C at 25°C, discharged to 2.5 V at a constant current of 0.2 C, and then charged to 4.25 V at a constant current of 0.2 C. After that, each lithium secondary battery was disassembled, and only the positive electrode was separated, and the positive electrode was set in a battery shell for DSC, and an electrolyte in which 1 M LiPF6 was dissolved in an organic solvent (EC / EMC / DMC (3 / 3 / 4, volume %) was added to the battery shell for DSC, so that the amount of the electrolyte was 30 parts by weight based on 100 parts by weight of the total positive electrode, thereby preparing a battery for DSC. Thermal stability was evaluated by increasing the temperature from 25°C to 400°C at a rate of 10°C / min, setting the highest value of the first exothermic peak that appeared during heating as the starting peak, and the starting temperature (Onset Temp.) is shown in Table 2 below.

[0211]

[0212] Referring to Table 2, it can be confirmed that the battery including the positive electrode active materials of Examples 1 to 3 has high initial efficiency, low initial resistance, and excellent cycle characteristics and thermal stability. Specifically, it can be confirmed that the battery including the positive electrode active material of Example 1 has higher initial efficiency, lower initial resistance, and lower resistance increase rate than the battery including the positive electrode active materials of Comparative Examples 1 and 4 in which only the doping method is different. In addition, it can be confirmed that the battery including the positive electrode active material of Example 2 has higher initial efficiency, lower initial resistance, and lower resistance increase rate than the battery including the positive electrode active material of Comparative Example 2 in which only the doping method is different.

[0213] The reason for this is that in the case where zirconium is first doped into a composite transition metal hydroxide precursor as in the method for preparing a positive electrode active material according to the present invention, that is, in the case where zirconium is first doped during the preparation of the composite transition metal hydroxide, since not only the distribution of zirconium but also the distribution of aluminum added in the steps of mixing the precursor and the lithium-containing raw material and sintering the mixture can be controlled, as a result, a positive electrode active material is prepared in which the weight ratio of aluminum present in the interior to aluminum present on the surface is greater than 1.0 and the weight ratio of zirconium present in the interior to zirconium present on the surface is greater than 1.0.

Claims

1. A method for preparing a positive electrode active material, the method The following steps are involved: (A) preparing a zirconium-containing composite transition metal hydroxide by adding a transition metal-containing solution containing at least one selected from nickel, cobalt and manganese, a zirconium-containing raw material, an ammonium cation complexing agent, and an alkaline solution into a reactor and performing a coprecipitation reaction; and (B) preparing a lithium composite transition metal oxide by mixing the zirconium-containing composite transition metal hydroxide with a lithium-containing raw material and an aluminum-containing raw material and sintering the mixture, The lithium composite transition metal oxide contains zirconium, aluminum, and at least one selected from nickel, cobalt, and manganese.

2. The method according to claim 1, wherein the zirconium-containing raw material is at least one selected from zirconium hydroxide, zirconium sulfate, zirconium acetate, zirconium nitrate, zirconium halide, zirconium sulfide and zirconium oxyhydroxide. 3 . The method according to claim 1 , wherein the zirconium-containing raw material is added so that the amount of zirconium is 1,000 ppm to 9,000 ppm based on the total weight of the zirconium-containing composite transition metal hydroxide.

4. The method according to claim 1, wherein the aluminum-containing raw material is at least one selected from aluminum hydroxide, aluminum oxide, aluminum sulfate, aluminum acetate, aluminum nitrate, aluminum halide, aluminum sulfide and aluminum oxyhydroxide. 5 . The method according to claim 1 , wherein the aluminum-containing raw material is added so that an amount of aluminum is 1,000 ppm to 9,000 ppm based on the total weight of the lithium composite transition metal oxide.

6. The method according to claim 1, wherein the sintering of step (B) is performed at a temperature of 700°C to 800°C.

7. A positive electrode active material, comprising a lithium composite transition metal oxide, wherein the lithium composite transition metal oxide comprises zirconium, aluminum, and at least one selected from nickel, cobalt and manganese, wherein the weight ratio of aluminum present in the interior to aluminum present on the surface is greater than 1.0, and The weight ratio of zirconium present in the interior to zirconium present on the surface is greater than 1.

0. 8 . The positive electrode active material according to claim 7 , wherein the zirconium content of the lithium composite transition metal oxide is 1,000 ppm to 9,000 ppm based on the total weight. 9 . The positive electrode active material according to claim 7 , wherein the aluminum content of the lithium composite transition metal oxide is 1,000 ppm to 9,000 ppm based on the total weight.

10. The positive electrode active material according to claim 7, wherein the average particle size (D 50 ) is 3 μm to 20 μm. 11 . A positive electrode comprising the positive electrode active material according to claim 7 . 12 . A lithium secondary battery comprising the positive electrode according to claim 11 .